Żywy symbol świetności – obraz Uniwersytetu Wileńskiego w pamięci Polaków guberni północno-zachodnich w świetle pamiętnika Witolda Małcużyńskiego - Korybut-Marciniak, Maria (Przegląd Wschodnioeuropejski, 2026)
The article analyzes how Vilnius University (1803-1832) functioned as a figure of memory for Poles in the Northwestern Governorates of the Russian Empire after its suppression in 1832. The primary source is the manuscript memoir of Witold Małcużyński, which records the recollections of his father, Stanisław – a graduate of a teachers’ seminary and later a schoolteacher. The study combines ego-document analysis with microhistory and cultural memory studies, juxtaposing the narrative with the context of Russification following the uprisings of 1830/31 and 1863/64. Based on the manuscript memoir, it reconstructs the channels through which the memory of Vilnius University was transmitted (family storytelling, teachers’ milieus) as well as the repertoire of images of the university that sustained communal identity into the early twentieth century. The analysis indicates that this memory functioned as a symbolic resource and a point of reference for Poles in the Northwestern Governorates amid intensifying repressions by the partitioning power.